Atomic layer deposition of ultra-trace Pt catalysts onto a titanium nitride nanowire array for electrocatalytic methanol oxidation. Issue 88 (18th October 2019) - Sun, Junwei; Wang, Xin; Song, Yanyan; Wang, Qianqian; Song, Yumei; Yuan, Ding; Zhang, Lixue
Abstract : Atomic layer deposition of ultra-trace Pt onto three-dimensional titanium nitride nanowire array was realized, and the obtained catalyst shows a much larger mass current density than commercial Pt/C towards electrocatalytic methanol oxidation. Abstract : Developing efficient and durable catalysts for methanol oxidation is of great significance for direct methanol fuel cells. Herein, we realized the deposition of ultra-trace Pt nanoparticles by atomic layer deposition (ALD) onto a three-dimensional (3D) titanium nitride (TiN) nanowire array grown on carbon cloth (CC), in which the 3D TiN nanowires provide a stable platform for the Pt nanoparticles, besides the inherent properties of high corrosion resistance and conductivity. Owing to the superior characteristics of the 3D TiN nanostructure as the support material and the strong interaction between Pt and TiN, the Pt nanoparticles on the TiN nanowire array show an enhanced electrocatalytic activity toward methanol oxidation compared to a commercial Pt/C catalyst. This work provides an effective strategy to fabricate 3D high-performance electrocatalysts for future energy applications.